Fetal transverse cerebellar diameter measurement in intrauterine growth restriction: a more accurate parameter for gestational age assessment at term - Mourya, Saroj; Mourya, Harish Kumar; Jain, Vimla; Verma, Manoj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Assessment of fetal gestational age (GA) is an essential part of obstetric USG. Accurate knowledge of fetal GA is important to facilitate the best possible prenatal care and successful pregnancy outcome. For the estimation of GA the commonly used parameters in third trimester are:- BPD, HC, AC and FL. As all these parameters are affected by fetal growth disorders and fetal position. TCD can be used as another parameter for the estimation of GA in growth restricted fetuses. Methods: This study was conducted at Mahila Chikitsalaya Sanganeri Gate; SMS Medical College Jaipur from July 2005 to September 2006. A total of 80 pregnant women in third trimester with singleton pregnancy including 40 pregnant women with known cases of IUGR and 40 AGA fetuses were studied for TCD measure. Results: Correlation coefficient between TCD and gestational age was highly significant and no significant difference was found in TCD of AGA and IUGR fetuses. Conclusions: TCD measurement can be used as more reliable parameter for accurate estimation of gestational age in IUGR fetuses in third trimester.